Planning for work: Exploring the relationship between contraceptive use and women’s sector-specific employment in India - McDougal, Lotus (PLoS One, 2021)
While the health-related benefits of contraceptive use for women are well documented, potential social benefits, including enabling women’s employment, have not been well researched. We examine the relationship between contraceptive use and women’s employment in India, a country where both factors have remained relatively static over the past ten years. We use data from India’s 2015–16 National Family Health Survey to test the association between current contraceptive use (none, sterilization, IUD, condom, pill, rhythm method or withdrawal) and current employment status (none, professional, clerical or sales, agricultural, services or production) with multivariable, multinomial regression; variable selection was guided by a directed acyclic graph. More than three-quarters of women in this sample were currently using contraception; sterilization was most common. Women who were sterilized or chose traditional contraception, relative to those not using contraception, were more likely to be employed in the agricultural and production sectors, versus not being employed (sterilization adjusted relative risk ratio [aRRR] = 1.5, p<0.001 for both agricultural and production sectors; rhythm aRRR = 1.5, p = 0.01 for agriculture; withdrawal aRRR = 1.5, p = 0.02 for production). In contrast, women with IUDs, compared to those who not using contraception, were more likely to be employed in the professional sector versus not being employed (aRRR = 1.9, p = 0.01). The associations between current contraceptive use and employment were heterogeneous across methods and sectors, though in no case was contraceptive use significantly associated with lower relative probabilities of employment. Policies designed to support women’s access to contraception should consider the sector-specific employment of the populations they target.